Medical-psychological rehabilitation of the military men who have received wounds during carrying out of counterterrorist operation in Dagestan in 1999 - A. S. Ibragimova; A. M. Amirov (Юг России: экология, развитие)
The experience of the complex medico-psychological rehabilitation of 110 military men with consequences of the combat traumas is presented. The preferable criteria during the selection of rehabilitative methods depending on the efficiency of the differentiated approach to their use, sequence and duration of the influence, combinability have been defined. The high efficiency and practicability of the use of the method of the bio-acoustic psycho-correction in rehabilitations of wounded people with different levels of the breaches of psychic health has been shown.